PENGARUH E-SERVICE QUALITY, BRAND IMAGE, & HARGA TERHADAP KEPUASAN PELANGGAN PADA TRAVELOKA DI JAKARTA SELATAN - Fahriza Putra Shalihan, Fahriza (2022)
Traveloka is a start-up company that is developing one of the business of booking airline tickets. During the post-covid-19 recovery period, changes in tourist behavior, especially the millennial generation, resulted in fierce competition among online travel agents. So the purpose of this study was to determine: the effect of e-service quality, brand image, & price on Traveloka customer satisfaction in Jakarta Selatan . The approach used in this study is quantitative with a population of Traveloka users in South Jakarta. The sample used was 100 respondents with non-probability sampling by purposive sampling as a sampling technique of 100 samples. Data were collected by questionnaire and using SPSS (Statistical Package for the Social Sciences) version 25.00 application. Regression Model from inferential analaysis is Y=-2,852+0,321X_1+0,311X_2+0,252X_3. The results show that: (1) There is an influence between E-Service Quality on Traveloka customer satisfaction and significant (2) There is an influence of Brand Image on Traveloka customer satisfaction and significant (3) There is an influence between Price and Quality on Traveloka customer satisfaction andvsignificant ( 4) There is an effect of E-Service Quality, Brand Image, & Price on Traveloka customer satisfaction simultaneously and significant.